Modelling key variables for understanding the effects of grazing and nutrient recycling by zooplankton on the freshwater microbial loop - Schenone, Luca (2021)
1. Pelagic microbial food webs are structured by zooplankton through grazing and nutrient recycling. Cladocerans and copepods are assumed to have different effects on the microbial loop by grazing on different prey sizes and releasing phos- phorus (P) differentially. Here, we assessed this effect of differential zooplankton grazing and nutrient recycling on microbial loop dynamics using a combination of experimental and modelling approaches. 2. We performed field incubation experiments in an oligotrophic mountain lake (north-Patagonian Andes) using the natural microbial community and the two dominant zooplankton taxa: a cladoceran (Diaphanosoma chilense) and a copepod (Boeckella gibbosa). The effect of zooplankton grazing and nutrient recycling were assessed separately in different treatments with direct and indirect zooplankton presence, respectively. We built a mechanistic model to estimate zooplankton grazing and P recycling and prey P quotas. The model was parameterised with the results from our field experiment and with prior information from size-based traits and zooplankton C:P using a Bayesian approach. Laboratory experiments for zooplankton P excretion were also performed to test the predictive accuracy of our model. 3. Our model showed that copepods and cladocerans have contrasting effects on the microbial loop. Diaphanosoma chilense grazed mainly on picoplankton while B. gibbosa grazed on nanoflagellates and algae. Diaphanosoma chilense reduced the biomass and increased P quota of picoplankton, and reduced the P quota of nanoflagellates. In contrast, B. gibbosa released more P, increasing the picoplankton biomass and reducing the biomass of nanoflagellates, but increasing its P quota. 4. Based on our experimental and model results, copepod grazing favours higher Pacquisition rates for cladocerans by releasing more P for picoplankton. By contrast, cladocerans would have a mixed effect on the main food items of copepods by increasing P quotas of the strict osmotrophic algae but decreasing P quotas of nanoflagellates. 5. Our mechanistic model is useful to quantitatively assess key planktonic variables, which are usually difficult to measure in the field, such as zooplankton P excretion